What is driving wealth inequality in the United States of America? The role of productivity, taxation and skills - Ekkehard Ernst; François Langot; Rossana Merola; Fabien Tripier (International Labour Organization (ILO), 2024)
Out of four major structural changes affecting the US economy - namely a rising share of skilled workers, skill-biased technological change, decreasing progressiveness of taxation and productivity slowdown - we show that the decline in productivity growth not only is the main driver of the widening wealth disparities observed in the United States of America over the past few decades, but is also the only mechanism that can explain inequalities both within and between skill groups.
Keywords: 330; skills; inequality; productivity; taxation; fiscal policy